Intensification of hydrocarbons extraction by pulse-wave methods - V. G. Shevchenko, Ya. B. Tarko A. F. Bulat, Ye. І. Kryzhanivskyy, G. O. Shevchenko (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
The construction of the vibration-pulse generator for the impact into the liquid filled well are proposed. The vibration-pulsegenerator excites a multifrequency oscillation spectrum in the frequency range from 0 to 20 kHz or more. Due to the continuouswide spectrum of frequencies, excited by the generator, the pressure pulses spreading through the well to the rock formation andcoinciding with the local frequencies of the local structures of a tensed rock massif excite resonances of the layers structures with the release of their internal energy in the local volume of the massif. As a result, the redistribution of the stressed state of themassif towards the alignment of internal stresses is due to the micro-displacement of local structures that form a massif, with the formation of new filtration channels, the evolution of microcracks and the purification of existing filtration channels. In case ofdeviation of the multifrequency spectrum of pressure pulses, the waves of hydrodynamic pressure of different lengths will spreadin the well from the outfall, where the vibration impulse generator is installed, to the face. At the same time, with the increase indistance, the contribution of low-frequency components into the oscillation energy will increase. It is advisable to combine the vibration impulse with the technologies of creating high depressions and pressure repressions, which will greatly increase the efficiency of the intensification works in the wells of different categories.